Challenges facing small-firm managers in growing manufacturing firms - Joakim Tell (Journal of Innovation and Entrepreneurship, 2015)
Purpose: The purpose of this article is to better understand the management challenges facing managers in small growing firms. Design/methodology/approach: Empirical data have been collected in Sweden through structured observations (approx. 20,000 min) of the working days of six top managers in fast- and six managers in slow-growing small manufacturing firms in order to compare managerial behaviour in two different contexts. Findings: Managers in small firms are engaged in many different activities, but a small number of activities tend to take up the majority of the managers' time. These activities can be classified as either operational or administrative. There are notably small differences (both in variance and differentiation) between the behaviours of managers in fast- and slow-growing firms; actually, there are more similarities than differences. There is also surprisingly little time spent by the managers on strategic work, even in the group of fast-growing firms. This might explain why growth and innovation in many cases come to a halt or even decline in these firms and represents such a challenge for the managers when they do not prioritize strategic work. Originality/value: The study shows that managerial work in small firms is characterized by a generic behaviour and that the managers mainly use a habitual and limited behavioural repertoire. Many managers have difficulties in changing their mainly operational and administrative behaviour and thus the underlying strategy of the firm. They are "stuck" in a path-dependency mindset, even though the development of the firm might require another strategy taken by the manager, as a response to meet environmental demands.
Keywords: 650; Managerial strategies; Observational studies; Habitual and limited behaviour; Path dependency; Innovation; Networks